IMPLEMENTASI METODE AGILE PADA APLIKASI SISTEM PENDAFTARAN SISWA BARU BERBASIS WEB DENGAN NOTIFIKASI WHATSAPP (STUDI KASUS : PAUD NURUSSYIFA) - Susanna Dwi Yulianti Kusuma; Rizky Febriansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PAUD Nurussyifa is one of the educational institutions, where this institution educates children at an early age in building their character and personality to become better human beings. Every year there are approximately 80 prospective students who register so to process all the existing data takes approximately one week. In the management of new student registration, it is still the conventional way where prospective registrants come to take the registration form to the registration counter which then the data is inputted by the staff into Microsoft Excel which is felt to also hinder the registration process so that data redundancy often occurs. and delays in reporting. To reduce these problems, it is necessary to have a system that is competitive, which can make it easier for prospective registrants to register easily, quickly, and efficiently. The method used in making this information system application uses the agile method, this method can be used to design and analyze the implementation of the agile method on a web-based new student registration information system application with whatsapp notifications (case study: PAUD Nurussyifa). The results of this study indicate that the use of a web-based new student registration information system application with WhatsApp notifications has accommodated the staff in charge of making reports that do not take too long and can also minimize the occurrence of data redundancy in managing registrant data more quickly, accurately and efficiently.